An introduction to statistical concepts - Lomax, Richard G. (Psychology Press, 2007)
Intended for the second or intermediate course in statistics and/or behavioural science departments, this book covers various ANOVA and regression models. It also includes an examination of the various procedures and necessary assumptions, tips on developing an APA style write-up, and sample SPSS output.